PENGARUH LOKASI DAN KUALITAS JASA TERHADAP KEPUASAN NASABAH KREDIT CEPAT AMAN - Sriwati Sriwati (Universitas Riau Kepulauan, 2017)
The purpose of this research is to determine and analyze the influence of location and service quality to the customer satisfaction of product Kredit Cepat Aman (KCA) at PT Pegadaian (Persero) CPP Bengkong UPC Pondok Asri Batam. The population that used in this research is the customers that have transaction at PT Pegadaian (Persero) CPP Pondok Asri Batam on April 2013 amounting to 645 customers. While the sample are 86 obtained from the calculation using the Slovin formula. This study was conducted by using multiple linear regression with quantitative analyzes, t-test (partial), F test (simultaneous) and coefficient of determination (R2). Based on the research results can be concluded: that location variable has influence but not significant to customers satisfaction but service quality variable has positive influence to customers satisfaction partially. Service quality variable becomes dominant variable which have influence to the costumers satisfaction based on calculations the analysis standardized of coefficients beta has the greatest value. Conclusion of this research is location and service quality as important variables that influence to customers satisfaction. However, it is suggested to the employees of PT Pegadaian (Persero) CPP Bengkong UPC Pondok Asri Batam have to maintain the service that have given to the customers and also upgrade it to gain better customers satisfaction.